Correct Solvability of a Nonlocal Multipoint (in Time) Problem for One Class of Evolutionary Equations - Horodets’kyi, V. V.; Martynyuk, O. V.; Petryshyn, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study properties of a fundamental solution of a nonlocal multipoint (with respect to time) problem for evolution equations with pseudo-Bessel operators constructed on the basis of constant symbols. The correct solvability of this problem in the class of generalized functions of distribution type is proved.